Criminal deportation : the unintended impact of U.S. anti-crime anti-terrorism policy along its third border - Griffin, Clifford E (2002)
Describes the domestic context within which U.S. anti-crime, anti-terrorism policy manifests itself in a more aggressive criminal deportation policy - one that remains contentious within U.S.-Caribbean relations. Assesses the impact of this intermestic policy programme on Caribbean countries by focusing on Barbados, Belize and Trinidad and Tobago.